THE URGENCY OF HIGHER EDUCATION QUALITY MANAGEMENT IN IMPROVING SOFTSKILLS OF UNZAH PROBOLINGGO JATIM STUDENTS - Abdillah, Mahmudi; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Cakrawala Pedagogik, 2024)
Higher education quality management must be able to provide quality programs and services so as to encourage increased utilization of student graduate output in order to encourage the realization of quality services. The SCL method must be able to change the mindset of students' learning systems, namely; 1) knowledge is seen as something that is ready-made, just transferred from lecturer to student, becoming knowledge or the result of the transformation of someone who learns; 2) learning to receive knowledge (passive-receptive), which is a process of seeking and constructing (forming) active and specific knowledge; and 3) carry out an instruction that has been designed, then carry out various strategies that can help students learn. The SCL method approach to improving Unzah students' soft skills emphasizes individual interests, needs and abilities, namely the learning model of giving priority to continuing to explore their intrinsic motivation in building a society that likes learning. while improving the quality of human resources needed by society and being able to adapt to changes and developments over time.